HUBUNGAN TINGKAT PENDIDIKAN DENGAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DI WILAYAH PUTRA PONDOK PESANTREN ALQODIRI JEMBER - Eka Suryaningtyas; Ide Rocky (MEDICAL JURNAL OF AL-QODIRI, 2019)
Latar belakang: Perilaku Hidup Bersih dan Sehat (PHBS) is a set of behaviors practiced on the basis of awareness and can help itself in the field of health and realize public health. The purpose of this research is to know, identify and analyze Relation Education Level With Perilaku Hidup Bersih dan Sehat (PHBS) in the Boys English Camp area of Al-Qodiri Boarding School in Jember. Metode: This research design using Corelative design, approach Cross Sectional. In this study is done only once. By observing the education level and measurement of Perilaku Hidup Bersih dan Sehat (PHBS). The respondents are all residents of English Camp area of Al-Qodiri Boarding School in Jember as much as 61 Santri. With Total Sampling. The study was conducted on April 07, in the Boys English Camp area of Al-Qodiri Boarding School in Jember Hasil: Based on the result of the research, most of education level is SMA equal to 35 students (57,4%) and most of Perilaku Hidup Bersih dan Sehat (PHBS) as much as 49 santri (80,3%). After analyzing the data using Kendall's Tau, the result of p value: 0.000 <0.05 concluded H1 accepted, it means there is Relation of Education Level With Perilaku Hidup Bersih dan Sehat (PHBS) ) in the Boys English Camp area of Al-Qodiri Boarding School in Jember Kesimpulan: Based on the results of research, the higher the education level of santri, so better its Perilaku Hidup Bersih dan Sehat (PHBS).